Kualitas Pelayanan Publik pada Pembuatan Akta Kelahiran di Dinas Kependudukan dan Pencatatan Sipil Kota Gorontalo - Rahmat Rifki Towana; Ismet Sulila; Yakob Noho Nani (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
This study aims to determine and analyze the Quality of Public Services in Making Birth Certificates at the Population and Civil Registration Office of Gorontalo City. Viewed from the aspects: (1) Tangible (Physical Evidence), (2) Reliability (Reliability), (3) Responsiveness (Responsiveness), (4) Assurance (Guarantee), (5) Empathy (Empathy). This research method uses a Qualitative Approach with a Descriptive type. Data collection techniques used in this study are observation, interviews, and documentation. The results of the study indicate that in general the quality of public services in making birth certificates at the Population and Civil Registration Office of Gorontalo City has been running well, although there are still some obstacles. In the Tangible dimension, the infrastructure is adequate but still needs to be updated on technological devices. In the Reliability dimension, the service has followed the established procedures and completion times, although sometimes hampered by system disruptions. The Responsiveness dimension shows that employees are quite responsive in responding to community needs, but need to increase effectiveness when queues are high. In the Assurance dimension, employees are competent and maintain data security, supported by technical training in population administration management. Meanwhile, in the Empathy dimension, employees are friendly and caring, although individual attention to the public is reduced during peak hours.